Temperature extreme records: World Meteorological Organization metrological and meteorological evaluation of the 54.0°C observations in Mitribah, Kuwait and Turbat, Pakistan in 2016/2017. (17th June 2019) - Merlone, Andrea; Al‐Dashti, Hassan; Faisal, Nadeem; Cerveny, Randall S.; AlSarmi, Said; Bessemoulin, Pierre; Brunet, Manola; Driouech, Fatima; Khalatyan, Yelena; Peterson, Thomas C.; Rahimzadeh, Fatemeh; Trewin, Blair; et al.
Abstract: A World Meteorological Organization (WMO) committee officially evaluated temperature record extremes of 54.0°C at two locations, one in Mitribah, Kuwait on July 21, 2016 and a second in Turbat, Pakistan on May 28, 2017. The committee agreed that quantity and quality of documentation of both observations were excellent. Additional metrological testing of the equipment focused on three aspects: the calibration of both thermometers, an effort to estimate the factors influencing the measurements and a direct comparison of the two thermometers when exposed simultaneously to 54°C. The metrological analysis's conclusion for the Mitribah value is a temperature estimated to be 53.87°C with an expanded uncertainty of ±0.08°C. Correspondingly, for the Turbat value the temperature is estimated to be 53.72°C with an expanded uncertainty of ±0.40°C. Following that analysis, the committee recommended acceptance of the calibrated observations to the first decimal digit such that the Mitribah observation is accepted as 53.9 ± 0.1°C and the Turbat as 53.7 ± 0.4°C. The Mitribah, Kuwait temperature is now accepted by the WMO as the highest temperature ever recorded for Asia (WMO RA II) and the two observations are the third (tied within uncertainty limits) and fourth highest WMO‐recognized temperature extremes and, significantly, they are the highest, officially recognized temperatures to have been recorded in the last 76 years. This evaluation has involved the most extensive temperature extremes analysis ever to be undertaken by an international evaluation committee of the WMO CCl Archive of Weather and Climate Extremes. Abstract : A World Meteorological Organization (WMO) committee officially evaluated temperature record extremes of 54.0°C at two locations, one in Mitribah, Kuwait on July 21, 2016 and a second in Turbat, Pakistan on May 28, 2017. Metrological testing concluded the Mitribah value is a temperature estimated to be 53.87°C with an expanded uncertainty of ±0.08°C. Correspondingly, for the Turbat value the temperature is estimated to be 53.72°C with an expanded uncertainty of ±0.40°C.